2013
DOI: 10.1111/febs.12299
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 and c‐Myc regulate transcription of BMI1 in nasopharyngeal carcinoma

Abstract: B-lymphoma mouse Moloney leukemia virus insertion region 1 (Bmi1), a member of the polycomb group, has elevated expression and is involved in the pathogenesis of various aggressive cancers, including nasopharyngeal carcinoma (NPC). To date, the mechanisms underlying the high expression of Bmi1 in NPC remain obscure. To gain new insights into the transcriptional regulation of BMI1, we cloned and characterized the promoter region of BMI1. Luciferase reporter assays demonstrated that the region from À783 to +375 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…Thus, the results underscore the importance of Bmi-1 targeting in combination with irradiation in nasopharyngeal neoplasm therapy. This finding is consistent with the reports of Wang et al (13) and Alajez et al (15).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, the results underscore the importance of Bmi-1 targeting in combination with irradiation in nasopharyngeal neoplasm therapy. This finding is consistent with the reports of Wang et al (13) and Alajez et al (15).…”
Section: Discussionsupporting
confidence: 94%
“…B-cell-specific Moloney murine leukemia virus integration site 1 (Bmi-1), a member of the Polycomb family of transcriptional repressors, is essential for maintaining the self-renewal and differentiation of human stem cells (4)(5)(6)(7). Bmi-1 has been demonstrated to be overexpressed in various of tumors (8), such as lung (9), breast (10) and prostate cancer (11), esophageal carcinoma (12) and NPC (13). Bmi-1 inhibition has been shown to sensitize those tumor cells to radiation (10,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Western blot was performed as previously described [32]. Briefly, cells were harvested and lysed in RIPA buffer containing protein inhibitor cocktail (F. Hoffmann-La Roche Ltd, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…We previously identified Sp1 as an important transcription factor for oncogenes in NPC, including B-lymphoma mouse Moloney leukemia virus insertion region 1 (Bmi1) and centromere protein H (CENPH), but the role of Sp1 in the development of NPC remains obscure [32],[33]. In the present study, we found the level of Sp1 was elevated in advanced NPC tissues and silencing of Sp1 significantly inhibited cell proliferation, clonogenicity, anchorage-independent growth and the stem-cell like phenotype of NPC cells, suggesting Sp1 as a potential therapeutic target for NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, AATF has the potential to regulate several genes either through STAT3 or Akt 1. At this stage, it is pertinent to note that: a) IFN-γ has been shown to up-regulate the expression of genes coding for KLF4 and p53 [11,12] as well as down-regulate the c-myc gene transcription [13]; b) the tumor suppressor p53 has been found to up-regulate the expression of genes coding for KLF4 and MDM2 coupled with down-regulation of genes coding for C-myc, NFkB and IFN-γ [14][15][16][17][18]; c) the transcriptional factors E2F and C-myc were found induce the expression of genes coding for AATF [2,19] and polycomb group protein [20,21] Bmi-1 which, in turn, ensured sustained NFkB activation [22]; d) KLF4 was found to suppress SP1-dependent genes [19,21,23] coding for AATF, Bmi-1 and UCP2; e) C-myc has been shown to inhibit MDM2 protein through its ability to induce the expression of p19 ARF gene [24]. Taken together these findings precipitate the importance of AATF as the most crucial and critical cellcycle regulator as far was cell division is concerned.…”
Section: Aatf Interactome and Cell Decisionmentioning
confidence: 99%